Digitalisation in the lives of urban migrants: Evidence from Bogota - Charles Martin-Shields; Sonia Camacho; Rodrigo Taborda; Constantin Ruhe (Deutsches Institut für Entwicklungspolitik (DIE), 2019)
As increased migration, particularly to urban centres, and digitalisation play a greater role in development cooperation, more research on how these phenomena interact will become critical. Information communication technologies (ICTs) offer pathways for potentially making it easier for migrants to settle in, whether it be through e-government programmes or by accessing social networks that can help in finding housing and work. To better understand how ICTs fit into urban migrants' lives, we gathered new survey data in Bogota comparing how long-term residents, short-term residents, and Venezuelan migrants access and use ICTs. We identified a new factor that influences internet access among migrants after controlling for economic and social factors: duration of time in a neighbourhood. While migrants initially lag behind their neighbours in ICT and internet access, the longer they stay in one neighbourhood, the more likely they are to gain access to these technologies. Indeed, over time, our data shows that migrants become more likely than their neighbours to gain access to ICTs and the internet when they continue to stay in the same neighbourhood. Our results also show that uptake of e-government services remains a challenge. Citizens generally do not interact with their governments more than a few times a year, and migrants may not interact at all. Especially when working with vulnerable or "hidden" populations, development organisations need to put significant resources into education and outreach so that the populations they are trying to reach know about e-government services, and their value. The data collected in Bogota paints a potentially positive picture about using ICTs with migrants and migrant communities. By effectively engaging migrants early on and meeting basic initial needs such as housing or access to identification, development and humanitarian agencies could help migrants gain greater access to ICTs and make use of e-government platforms.
Keywords: 320; Migration; Digitalisation; E-government; Colombia